2018
DOI: 10.1038/s41467-018-04871-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for terminal loop recognition and stimulation of pri-miRNA-18a processing by hnRNP A1

Abstract: Post-transcriptional mechanisms play a predominant role in the control of microRNA (miRNA) production. Recognition of the terminal loop of precursor miRNAs by RNA-binding proteins (RBPs) influences their processing; however, the mechanistic basis for how levels of individual or subsets of miRNAs are regulated is mostly unexplored. We previously showed that hnRNP A1, an RBP implicated in many aspects of RNA processing, acts as an auxiliary factor that promotes the Microprocessor-mediated processing of pri-mir-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 81 publications
(101 reference statements)
3
93
0
2
Order By: Relevance
“…2B). This structural approach also confirmed that binding of hnRNP A1 to the TL induces an allosteric destabilization of base-pairing in the pri-mir-18a stem that promotes its processing (Kooshapur et al 2018). Of interest, binding of hnRNP A1 to the conserved TL of a precursor miRNA does not always result in enhanced miRNA processing.…”
Section: Role Of Rbps In the Regulation Of Mirna Biogenesismentioning
confidence: 55%
See 1 more Smart Citation
“…2B). This structural approach also confirmed that binding of hnRNP A1 to the TL induces an allosteric destabilization of base-pairing in the pri-mir-18a stem that promotes its processing (Kooshapur et al 2018). Of interest, binding of hnRNP A1 to the conserved TL of a precursor miRNA does not always result in enhanced miRNA processing.…”
Section: Role Of Rbps In the Regulation Of Mirna Biogenesismentioning
confidence: 55%
“…This can encompass different mechanisms, such as conformational changes and dynamic destabilization induced by the binding of these auxiliary factors. For example, the binding of hnRNP A1 or Rbfox proteins to pri-miRNAs leads to structural changes that affect Microprocessor binding and/or activity (Table 1; Chen et al 2016;Kooshapur et al 2018). Another common mechanism is antagonistic binding of the regulatory RBP to either a positive or negative regulator, as seen with the competitive binding of hnRNP A1 and KSRP to let-7 precursors in differentiated cells , or MBNL-1 antagonizing LIN28 binding to primir-1 (Rau et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our group have identified Lin28A as a negative regulator of the biogenesis of miR-9, through a distinct mechanism [60]. Additionally, hnRNP A1 negatively regulates let-7a levels [61][62][63]. We also found that miR-7 was modulated by cooperative effects between two RBPs, which will be described in detail later [64].…”
Section: Other Hts Targeting Lin28/let-7 and Conclusionmentioning
confidence: 58%
“…First, we wanted to assess whether the two dsRBD domains interact with each other despite the long 95-residue linker. Interdomain interactions have been reported for other RNA binding domains even in absence of RNA and could constitute a determinant of specificity by conformational selection (43,44).…”
Section: The Tandem Dsrbd Domains Of Mle Are Independent Structural Mmentioning
confidence: 98%